Assessment of endocrine disorders of the hypothalamicpituitary axis by nuclear medicine techniques - Schmidt, M.; Jockenhövel, F.; Theissen, P.; Dietlein, M.; Krone, W.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2002)
The following article reviews nuclear medicine techniques which can be used for assessment of endocrine disorders of the hypothalamic-pituitary axis. For planar and SPECT imaging somatostatin-receptor- and dopamine- D2-receptor-scintigraphy are the most widely distributed techniques. These nuclear medicine techniques may be indicated in selected cases to answer differential diagnostic problems. They can be helpful to search for presence and localization of receptor positive tissue. Furthermore they can detect metastasis in the rare cases of a pituitary carcinoma. Scintigraphy with Gallium-67 is suitable for further diagnostic evaluation in suspected hypophysitis. Other SPECT radiopharmaca do not have relevant clinical significance. F-18-FDG as PET radiopharmacon is not ideal because obvious pituitary adenomas could not be visualized. Other PET radiopharmaca including C-11-methionine, C-11-tyrosine, F-18-fluoroethylspiperone, C-11-methylspiperone, and C-11-raclopride are available in specialized centers only. Overall indications for nuclear medicine in studies for the assessment of endocrine disorders of the hypothalamic-pituitary-axis are rare. Original studies often report only about a small number of patients. According to the authors’ opinion the relevance of nuclear medicine in studies of clinically important endocrinologic fields, e. g. localization of small ACTH-producing pituitary adenomas, tumor localization in ectopic ACTH syndrome, localization of recurrent pituitary tissue, assessment of small incidentalomas, can not be definitely given yet.
Keywords: Pituitary disease; hypothalamic-pituitary axis; radionuclide imaging; SPECT; PET